A Recent Study on Flipbook as Media Implementation in Science Education in Digital Age: A Systematic Literature Review - Unayah, Habibatul; Rasyid, Muhammad; Suyanta, Suyanta; Wilujeng, Insih; Rahmawati, Laifa (Universitas Negeri Semarang, 2024)
Flipbooks are interesting reference books for student learning. The integration of digital media in education has become crucial in the digital age, and flipbooks have gained popularity as an interactive tool. This systematic literature review investigates the effectiveness and implementation of flipbooks in science education from 2017 to 2024. This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. We reviewed journal articles indexed in Scopus and Sinta, focusing on the use of flipbooks in science education. Our review highlights the effectiveness of flipbooks in improving student engagement, motivation, and learning outcomes in science education. The flipbook's interactive features, such as multimedia elements and simulations, have proven to support diverse learning styles. The adoption of flipbooks in science education shows promise for enhancing the digital literacy of students and educators. However, further empirical research is required to understand its long-term impacts and the best strategies for implementation.